Competition and Digital Game Design: a Self-Determination Theory Perspective - Moller, Arlen C; Kornfield, Rachel; Lu, Amy S (Interacting with computers, 2024)
Although competition is a common feature of digital games, nuances of when and why aspects of competition influence players' motivation and well-being have been surprisingly underexplored, especially through the lens of self-determination theory (SDT). In this critical review, we: (1) describe how a mini-theory of SDT, cognitive evaluation theory (CET), can help predict when and why aspects of competition will alternatively satisfy or frustrate basic psychological needs in digital games with downstream effects on players' motivation and well-being; (2) apply the Motivation, Engagement and Thriving in User Experience (METUX) model to outline ways competition in digital games can influence motivation and well-being at multiple levels; and (3) prioritize future research directions. Finally, we argue that digital games, given their diversity, adaptability and massive reach, represent an especially powerful context for studying competition, motivation and well-being.